Genotypic diversity of Pasteurella multocida isolates from pigs and poultry in Australia. Issue 10 (25th September 2018) - Turni, C; Singh, R; Blackall, PJ
Abstract : Objective: To investigate the genotype and diversity of Pasteurella multocida present in pig herds and to determine the extent of overlap with isolates from poultry flocks in Australia. Methods: A total of 43 isolates from pigs from different farms and regions of Australia were used in this study. A diverse collection of 41 poultry isolates, with 31 being previously characterised, was also used. The pig isolates and 10 poultry isolates were identified by species‐specific PCR assay, serotyped by the Heddleston scheme and genotyped by a multiplex PCR based on the lipopolysaccharide (LPS) outer core biosynthesis locus, repetitive element PCR fingerprinting (rep‐PCR) and multilocus sequence typing (MLST), with the latter being used on a subset of the isolates based on the rep‐PCR results. Results: Only 4 out of 8 recognised LPS genotypes were found in the pig isolates, with each isolate assigned to an LPS genotype. In contrast, 77% of the isolates were non‐typable or cross‐reacting in the Heddleston serotyping scheme. The rep‐PCR analysis recognised 20 patterns, yet only 16 sequence types (STs) were found and 4 were new STs. There were 5 STs (STs 7, 11, 20, 24 and 58) shared among the pig and poultry isolates. Conclusions: Although only limited numbers of isolates have been examined, there is evidence of a sharing of genotypes between Australian pigs and chickens. These findings have major implication for biosecurity measures with regard to minimising both direct (e.g. animal to animal) and in‐direct (e.g. shared staff or cross‐visitors) contact between poultry and pigs.